Acridine‐Thiosemicarbazones‐Stabilized Silver Nanoparticles as a Selective Sensor for Copper(II)‐Ion in Tap Water. Issue 30 (8th August 2019) - Ali, Imdad; Isaac, Ibanga Okon; Ahmed, Farid; Aslam, Fariha; Ali, Shujaat; Imran, Muhammad; Alharthy, Rima D.; Shah, Muhammad Raza; Malik, Muhammad Imran; Hameed, Abdul
Abstract: Environmental pollution due to heavy metals ions is becoming a serious threat to human health. In this study, we have synthesized acridine‐thiosemicarbazones‐stabilized silver nanoparticles (AT‐AgNPs) to explore their cation sensing ability and selectivity for detection copper(II)‐ion in aqueous system. Newly synthesized nanoparticle were characterized using various spectroscopic techniques such as ultraviolet–visible, Fourier‐transform infrared (FTIR), atomic force microscopy (AFM) and Zetasizer. The average size of the highly robust AT‐AgNPs was found to be in the range of 70–90 nm. The photophysical potential of AT‐AgNPs was explored using ultraviolet–visible spectroscopy. Addition of copper(II)‐ion induce significant quenching in the absorption intensity of AT‐AgNPs, whereas all other tested metals did not produce any detectable change in the UV‐visible spectrum. Further, the limit of detection (LOD) was determined by employing standard deviation method which is found to be 1  μ M with a R 2 equal to 0.9931. The synthesized AT‐AgNPs were highly selective for copper(II)‐ion in presence of other interferents like salts, and other metal ions. Moreover, the AT ‐AgNPs were effectively and efficiently employed for the same purpose in tap water. Abstract : Acridine‐Thiosemicarbazone based silver nanoparticles (AT‐AgNPs) were synthesized to explore their chemosensing ability and selectivity towards the cations detection. The addition of copper(II)‐ion induce significant quenching in the absorption intensity of AT‐AgNPs, whereas all other tested metals did not produce any detectable change in the ultraviolet (UV)‐visible spectrum. Moreover, the AT ‐AgNPs were also effectively employed for selective sensing of copper(II)‐ion in tap water.